The Influence of Transformational Leadership on Career Development of Generation Y and Z Employees Mediated by Job Satisfaction at PT.VCN - Veronica Norman Adinda Maha; Hery Winoto Tj; Soegeng Wahyoedi (MES Management Journal, 2025)
This study aims to examine the impact of transformational leadership on the career development of Generation Y and Z employees, mediated by job satisfaction at PT. VCN. The research was motivated by the perception among some employees of limited career advancement opportunities within the organization. Data was collected through questionnaires distributed to 108 employees meeting the study criteria, and the analysis was conducted using the SEM-PLS method.The findings reveal that transformational leadership significantly influences both job satisfaction and career development. Job satisfaction is demonstrated to be an effective mediator in the relationship between transformational leadership and career development. Although the direct impact of transformational leadership on career development is moderate (coefficient value: 2.744), the study underscores a clear relationship between leadership style and career advancement. Despite the implementation of transformational leadership, challenges related to career development remain prevalent among employees at PT. VCN. Factors such as self-confidence, work motivation, and recognition are critical to enhancing job satisfaction and fostering a more conducive environment for career growth. This research offers practical insights for the organization, emphasizing the need to optimize transformational leadership practices to boost job satisfaction and employee loyalty. By doing so, the company can better support the sustainable career development of its workforce.